Corporate social responsibility and the perception of the company: a review of the scientific literature - Roberto Luis Zegarra Reyes, José Santos Cortegana Salazar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims to systematically analyze Corporate Social Responsibility and its relationship with the perception it generates in stakeholders. A search for scientific papers was conducted using five academic databases: Ebsco host, ProQuest, Scielo, Google Scholar and Redalyc. The papers were chosen according to criteria such as: maximum age of ten years, relationship with the research problem, publication in Spanish and English language, leaving out documents that made reference to non- corporate social responsibility and others that could not be accessed. Twenty-six documents were analyzed, from which results were obtained on the dimensions of CSR that companies use and how these are perceived depending on the public researched, as well as research trends in this field. It was found that the ethical and social dimensions are those that generate the greatest positive impact on consumers and favor the corporate image. On the other hand, in certain cases the environmental dimension has no impact or even generates negative perceptions, but it is an important dimension for investors. It is worth mentioning the diversity of contexts analyzed, so generalizations may not be so precise.